Analisa Pengaruh Ukuran Mesh dan Curring Time Pada Komposit Serbuk Kayu Nyatoh Terhadap Pengujian Tarik - Somawardi, Somawardi; Akbar Rafsanjani, Alfarobbi; Yuliyanto, Yuliyanto; Sukanto, Sukanto (Manutech : Jurnal Teknologi Manufaktur, 2023)
Various types of trees grow in Indonesia, one of which is the Nyatoh tree. Uses: This nyatoh wood tree is very useful as a material for building houses, making furniture, and so on. In the process of processing nyatoh trees into finished materials, shavings or powder will be produced, but the use of shavings or powder has not been utilized optimally. So the rest of the process makes the surrounding environment dirty and unsightly. This composite material has the advantages of adjustable strength, excellent fatigue strength, corrosion resistance, light weight and very low production costs. The aim of this research is to determine the tensile test value of nyatoh wood powder composites at volume fractions of 5%, 10%, 15% with a mesh size factor of 100, 150, 200 and a curing time of 2 hours with a heating temperature of 60 ?, 80 ?, 100 ?. The research method used is the full factorial method. The composite material is made using the hand-lay-up method. The highest tensile strength value in this research was a 5% sample with a mesh size of 200 and a curing time temperature of 60 ? with a tensile test result of 30.60 Mpa. Meanwhile, the lowest tensile strength result was 10.97 Mpa at a powder fraction of 5% with a mesh size of 100 and a curing time with a temperature of 60 ?. The size of the mesh greatly influences the tensile testing, where the higher the mesh used, the tensile strength increases. Meanwhile the heating process (curring time) also has an influence, but not so big, the higher the temperature of the curing time will cause a decrease in tensile strength.